Fish passage ladders from Canoas Complex - Paranapanema River: evaluation of genetic structure maintenance of Salminus brasiliensis (Teleostei: Characiformes) - Lopes,Carla Martins (2007)
The aim of this study, utilizing RAPD techniques, was to determine the genetic variability of Salminus brasiliensis groups collected at passage ladders of the hydroelectric plants (HEP) Canoas I and Canoas II - Paranapanema River (Brazil), as well as to estimate the population structure through different parameters of genetic diversity. The data obtained allowed us to conclude that S. brasiliensis of the Canoas Complex has a moderate index of genetic variability ( > 42.00%) when compared to that of other migratory fish species. All genetic diversity analyses (distance = 0.015 and genetic identity = 0.985, F ST =0.018, AMOVA) were signs of low genetic differentiation, and they led to the clustering of S. brasiliensis from Canoas I and Canoas II. This suggests that the species is genetically structured as a single population. Some findings indicate that this population of S. brasiliensis comes from the Capivara Reservoir (Canoas I downstream), probably fed by the Tibagi and Cinzas Rivers. Literature data denote that after fish transposition by passage ladders of the Canoas Complex, the migratory species are not concluding the reproductive cycle. This mechanism, therefore, could be one more impact factor causing the depletion in downstream recruitment, which could in medium and long term be compromising the natural S. brasiliensis population in the middle Paranapanema River.